"Homosexual People Do Not Stand Outside of Socialist Society": Eingaben and the History of Homosexuality in East Germany. Issue 1 (1st March 2022) - Johnson, Jason
Abstract: This article centers on four petitions ( Eingaben ) presented to the East German Central Committee in the 1970s and 1980s by men attracted to other men. The East German legal apparatus required that the state address all petitions. An analysis of these Eingaben written by non-activists demonstrates a growing boldness to use the available legal structures to claim one's rights. The petitioners used the Eingaben system to assert their legitimacy as gdr citizens, forcing officials to deal with them as any other citizen. This article moreover calls for the still young field of East German homosexual history to more fully incorporate the untold number of Eingaben written by homosexuals in the former gdr . This would help to develop a more comprehensive historical narrative as such documents provide an invaluable and unique window into everyday life under socialism.